TISSUE THROMBOPLASTIN-INDUCED REVERSIBLE DIC AS AN IN VIVO MODEL OF THROMBIN GENERATION AND INHIBITION - Marbet, G A; Zbinden, B; Satiropas, P; Duckert, F (Thrombosis and Haemostasis, 1987)
We have tried a kinetical approach to characterize the dynamics of thrombin generation, thrombin action and heparin-enhanced inhibitors in vivo. Integrals (φ) of free thrombin concentration over time were calculated from fibrinogen decrease to characterize tissue thromboplastin-induced DIC in the dog. DIC with φ < 8nMmin was reversible. Dynamic thrombin inhibition (DTI), measured as pseudo-first order rate constant of thrombin inactivation by plasma (baseline DTI = 6.31± 0.79/min, n=30) increased to 68.69±59.98/min (n=7) with heparin (H) and to 22.48±14.91/min (n=5 with pentosan polysulfate (PPS). DTI correlated significantly with heparin doses (p< 0.002), and with the prolongation of APTT (p<0.0 2) and of prothrombin time (p < 0.05). The efficiency β of tissue thromboplastin (Tp) to trigger DIC ( φ per ml TP) was reduced from β =3.81±3.16nMmin/ml to 0.74±0.52nMmin/ml by H (p < 0.01) and to 1.16±1.10nMmin/ml (n.s.) by PPS. As expected from the product DTI.φ = 23.4 ± 13.8nM there was no detectable decrease of prothrombin, of the combined activity of antithrombin III + heparin cofactor II (ATHC) or of heparin cofactor II (HC, specific assay by dermatan sulfate activation) in reversible DIC without glycosaminoglycan protection. However, increasing doses of TP at constant PPS protection induced a statistically significant and persistent decrease of prothrombin by 17.6±9.91 and of HC by 20.4±8.81 indicating HC enhancement by PPS in vivo. The model is suitable for the study of glycosa-minoglycans and thrombin inhibitors.